Human Wildlife Conflicts and Livelihood Diversification among Kamnnarok National Reserve Adjacent Communities in Baringo County, Kenya - Togoch, K. H.; Irandu, M. E.; Thuita, T. (Africa Environmental Review Journal, 2018)
Increasing human populations and economic challenges are intensifying reliance by local communities on Wildlife Protected areas (WPAs) in marginal rangelands. Human wildlife conflicts in areas adjacent to Kamnarok National Reserve (NR)is an outcome of excessive resource extraction by adjacent household activities, declining food resources for wildlife and weak conservation governance by those in charge. The Kamnarok NR resources have supported livelihoods for adjacent communities as well as adversely affecting their lives and livelihoods through crop damages, livestock predation, property destruction and human injuries & even deaths. The adjacent communities have diversified livelihood portfolios for varied reasons including; risks aversion associated with wildlife conflicts, increased income, food security and for meeting household needs. Livelihood diversification is a positive undertaking and therefore Kamnarok NR adjacent households should be allowed and encouraged to diversify livelihoods as it enables them to co-exist harmoniously with wildlife and enhance their income portfolios